128 Desmosomal instability increases atrial arrhythmia susceptibility after endurance training. (June 2018) - Hepburn, Claire; Syeda, Fahima; Yu, Ting; Holmes, Andrew P; Roth, Victor Cardoso; Wright, Thomas; Kabir, Syeeda Nashitha; Menon, Priyanka; Wells, Simon; Vloumidi, Eleni; Apicella, Clara; Lutz, Susanne; et al.
Abstract : Background: Endurance training has recently been associated with increased risk of atrial fibrillation (AF). In patients with desmosomal dysfunction, exercise can promote disease progression and ventricular arrhythmias. We studied the effect of desmosomal dysfunction on atrial arrhythmia susceptibility in mice with reduced plakoglobin expression in heterozygous (Plako±) after endurance training. Methods: Wildtype (WT) and Plako ±young adult littermates underwent 8 weeks of incremental endurance swim training or sedentary lifestyle. The effects of training and Plako ±on atria were assessed using echocardiography, monophasic action potentials (MAP), transmembrane action potentials (TAPs), optical mapping, histology, RNA sequencing (RNAseq and RT-PCR. Data are expressed as mean ± SEM. Results: Endurance exercise increased atrial arrhythmias in Plako±hearts only (Plako±-sedentary 1/9 hearts; Plako±-trained 9/17; WT-sedentary 3/11; WT-trained 1/11). Training increased LA size in both genotypes (WT-sedentary 2.9 ± 0.1 mm2; WT-trained 3.5±0.2 mm2; Plako±-sedentary 2.9±0.1 mm2; Plako±-trained 3.6±0.2 mm2, p<0.05; n=24–40 per group sedentary vs. training). Training shortened both action potential duration (APD) and effective refractory period (ERP) in both genotypes (APD; WT-sedentary 22.6±0.7 ms; WT-trained 20.3±0.7 ms, p<0.05; Plako±-sedentary 23±0.6 ms; Plako±-trained 21.3±0.9 ms, p<0.05; ERP; WT-sedentary 41±5 ms; WT-trained 28±2 ms; Plako±-sedentary 31±3 ms; Plako±-trained 28±2 ms, p<0.05; n=9–17 per group sedentary vs. trained). Calcium relaxation times were prolonged in endurance exercise trained Plako±LA (WT-trained 24.5±0.9 ms; Plako±-trained 30.5±1.6 ms, p<0.05; n=5–10). Histological quantification of fibrosis, using PicroSirius red, in trained LA from WT and Plako±hearts did not show a difference between genotypes after training (mean collagen area fraction WT-trained 38±6% vs. Plako±-trained 32±5%). However, early analysis of RNAseq in Plako±-trained LA identified a potential upregulation of profibrotic pathways. Moreover, RNAseq identified further phenotype-dependent changes in gene expression of some interacting genes. RNAseq and RT-PCR confirmed decrease in plakoglobin (JUP) in cardiac tissue of Plako± (padj <0.05). Conclusion: Plakoglobin deficiency predisposes to changes in electrophysiological atrial function and atrial arrhythmias post-training. Prolonged calcium relaxation times albeit shortened APD could be proarrhythmic. Atrial arrhythmia susceptibility is associated with altered expression of genes involved in pro-fibrotic signalling in response to exercise endurance training.